Incorporating Higher-Order Thinking Skills In The Indonesian Language Curriculum At Islamic Religious Universities - Mirnawati, Mirnawati; Yaumi, Muhammad; Halimah, Andi; Mardiana, Mardiana; Ahmad, Djuwairiah; K, Munawir; Rosdiana, Rosdiana (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Learning Indonesian in higher education, especially at IAIN Palopo, faces significant challenges due to the lack of appropriate and effective teaching materials, so it is necessary to develop teaching materials based on higher-order thinking Skills (HOTS) to improve the quality of learning and students' language skills. This study aims to develop and evaluate Indonesian language teaching materials based on higher-order thinking Skills (HOTS) to improve the quality of learning and language skills of students at the Faculty of Tarbiyah and Teacher Training, IAIN Palopo. This study uses the Research and Development (R&D) method with the Borg and Gall design to develop Indonesian language teaching materials based on higher-order thinking Skills (HOTS) at the Faculty of Tarbiyah and Teacher Training, IAIN Palopo. The research process involves the development, validation by experts, and revision of teaching materials, with data collected through validation sheets and analyzed using the Aiken index to measure validity. This research has successfully developed Indonesian language teaching materials entitled "Indonesian Language for Higher Education: Learning Based on Higher Order Thinking Skills" integrated with HOTS. This book includes ten interrelated chapters covering the history and development of Indonesian as well as reading, writing, speaking, and listening skills. Three experts have validated This book through two stages and have successfully met the validity criteria regarding material, presentation, graphics, and language. The developed teaching materials show the potential to improve Indonesian language learning in higher education with the HOTS approach. This study provides a basis for further research on implementing these teaching materials in higher education environments.